(untitled) (Education in the 21st Century, 2023)
This article presents the clinical, psychological and pedagogical characteristics of mental retardation. We state, that without certain knowledge about the form, nature and degree of mental retardation of a child, it is impossible to organize and implement education, training, correctional-developmental, household and other types of work with him in proper, purposeful and effective manner. This determines the necessity for starting a comprehensive and in-depth study and analysis of the clinical, psychological and pedagogical characteristics of mental retardation. Based on a study of the results of research by local and foreign experts on the issues of mental retardation and the analysis of its classifications, the appropriate conclusions and the theoretical analysis of the clinical, psychological and pedagogical characteristics of mental retardation have been made. Since mental retardation significantly complicates the playing, educational, cognitive, labor and other activities of these children, it is obvious, that knowledge of the clinical, psychological and pedagogical characteristics of mental retardation will serve the basis for the effective organisation and conducting of educational, correctional and developmental work with these children in the family, in various types of preschool and educational institutions. The abovementioned points define the relevance of the present study, its theoretical and practical significance.